Fluorenone and triphenylamine based donor–acceptor–donor (D–A–D) for solution-processed organic light-emitting diodes. (1st June 2022) - Pham, Hong Duc; Banappanavar, Gangadhar S; Somasundaram, Sahadev; Deshmukh, Kedar D; Lim, Hyunsoo; Shukla, Atul; Ahmad, Viqar; McGregor, Sarah K M; Manzhos, Sergei; Lo, Shih-Chun; Kabra, Dinesh; Namdas, Ebinazar B; et al.
Abstract: In this work, we describe the design and synthesis of a novel, organic emissive small donor–acceptor–donor molecule, 3, 6-bis(4-(bis(4-methoxyphenyl)amino)phenyl)-9 H -fluoren-9-one, and its incorporation into functional organic light-emitting diode (OLED) devices. The molecule was developed through a three-step procedure with high yields using low-cost and commercially available materials. Photophysical analysis shows emission from both locally excited (LE) and intramolecular charge transfer (ICT) fluorescent states, leading to broad emission spectra with a high solution photoluminescence quantum yield of 73%. Time resolved and temperature dependent photoluminescence measurements were utilized to obtain insights about emission mechanism from LE and ICT states. The presence of broad emission was further confirmed using density functional theory calculations. After optimal design and selection of the film thickness and host matrix, an OLED using a solution-processed host: dopant emissive layer with 10 wt% dopant exhibited a maximum current efficiency, power efficiency and external quantum efficiency of 2.6 cd A −1, 2.5 lm W −1 and 1.5%, respectively.